The Judicial Control of environmental quality standards (Comentary on the decision by The Second Environmental Court on December 16th, 2015, Case 22-2014) - De la Fuente Castro, Osvaldo (Revista de Derecho Público, 2016)
The author analyzes the judgment of the Second Environmental Court on complaint against Decree N° 20 of 2013, Ministry of Environment, which “provides health-based national air quality standard for PM 10, in particular the values that define emergency and repeal Decree N° 59 of 1998, Ministry General Secretariat of the Presidency. In his critique, finds a weak conception of the principle of legality, which affects the interpretation offered by the court of the scope of judicial review exercised by the environmental courts. He also argues that much of the interpretive problems in this case, relating to access to justice and the duty to give reasons for administrative decision, can be resolved in the light of a system of administrative law, which belongs environmental law.